Identity formation of the modern lifestyle entrepreneur - Popp, Stephanie (2016)
Purpose- The purpose of this thesis is to explore the identity of lifestyle entrepreneurs in the Millennial demographic. Prior research is extensive on the construction of identity as well as lifestyle entrepreneurship as a discipline. However, there are gaps in research for the latest generation of entrepreneurs. Their approach to business, lifestyle, and work-life balance differs greatly from their predecessors. Aim- This thesis aims to capture the unique essence and identifying factors of lifestyle entrepreneurs who are in their mid-twenties to mid-thirties. The goal of the researcher is to contribute to the understanding and acceptance of the new age of business owners through accounts in their own words. Approach- The study is comprised of semi-structured interviews with 12 lifestyle entrepreneurs in the Millennial age range. The researcher conducted Interpretative Phenomenological Analysis to interpret the informant ́s understanding of meaning and impact of their work. Research Question- The focal research question is: What composes the identity of a lifestyle entrepreneur? Findings- The researcher concluded that in the modern business climate the two main factors are 1) Identity is more strongly formed in the space of what the entrepreneur does not want to do or become, rather than in dreams of what they want. 2) Modern lifestyle entrepreneurs are integrating technology into their identity. The level of technology usage of the informant offers insight into how they identify as an entrepreneur.